Grado de aceptación de los sistemas de evaluación digitales adaptados al uso de recursos tecnológicos educativos basados en Realidad Aumentada / Degree of acceptance of digital evaluation systems adapted to the use of educational technological resources based on Augmented Reality - Santiago Delgado-Rodríguez; Silvia Carrascal-Domínguez; Rebeca García-Fandiño (Revista Latinoamericana de Tecnología Educativa)
The use of immersive technologies, especially Augmented Reality (AR), is presently one of the main technological trends in the field of education. Some studies carried out in recent years in this field highlight that traditional evaluation systems continue to be used and raise the possibility of using adapted evaluation systems. This research, based on primary sources of information, seeks empirical evidence regarding the need to use digital evaluation systems adapted to technological resources in Science subjects and in stages of Compulsory Secondary Education. The methodology used is quantitative research based on the design and statistical analysis of the responses given by students to a questionnaire created ad hoc, administered to assess an AR educational resource used in class to explain a key concept in connection with the subject. The results obtained through the exploratory factorial analysis of the students’ answers reveal, as a latent construct, a high level of acceptance of the digital evaluation system used. The analysis of the data obtained in this study allows us to establish the hypothesis that a digital evaluation system adapted to the use of an immersive AR technological resource can generate a positive impact on the students' learning process.